Gurig National Park : the first ten years of joint management - Foster, David, 1948- (Report series (Australian Institute of Aboriginal and Torres Strait Islander Studies), 1997)
Assessment of the first ten years of operation of the Cobourg Act, under which Gurig National Park became the first National Park in Australia under joint management through a formal board of management structure; discusses employment opportunities; community facilties; commercial developments such as safari hunting, tourist operations, Seven Spirits Wilderness Resort.